PENGARUH WAKTU PENYIMPANAN SPESIMEN SPUTUM PADA SUHU RUANG TERHADAP HASIL PENILAIAN BAKTERI TAHAN ASAM (BTA) - Ni Wayan Desi Bintari (Jurnal Sains dan Teknologi Laboratorium Medik, 2021)
One of the ways to establish a diagnosis of pulmonary tuberculosis is through laboratory investigations. The quality of the specimen is known to greatly affect the results of the examination. In order to ensure good quality specimens, sputum from pulmonary tuberculosis patients should be examined immediately after collection. However, conditions in the field sometimes result in delays in testing. This study aims to determine whether or not there is an effect of storage time for sputum specimens at room temperature on the results of acid fast bacilli assessment. The research was conducted at Udayana Tingkat II General Hospital Denpasar in January-April 2020. Type of research was a pre experimental design with a one-shoot case study approach. Sputum storage was carried out for 24 hours and 48 hours at a temperature of 22-250C. Acid fast bacilli examination was carried out using the Ziehl Neelsen staining technique and acid fast bacilli assessment was carried out based on the IUATLD scale. The research data were analyzed for normality of the data and Friedman's test. The results showed that there were differences in the results of the acid fast bacilli assessment on specimens immediately examined and those stored at room temperature for 24 hours and 48 hours. Based on the Friedman test, it was found that the P value was 0.00 (P <0.05) so that it was concluded that there was an effect of storage time for sputum specimens at room temperature on the results of acid fast bacilli assessment.